Fighting Ebola with novel spore decontamination technologies for the military - Doona, Christopher J.; Feeherry, Florence E.; Kustin, Kenneth; Olinger, Gene G.; Setlow, Peter; Malkin, Alexander J.; Leighton, Terrance (Frontiers in Microbiology, 2015)
Abstract Recently, global public health organizations such as Doctors without Borders (MSF), the World Health Organization (WHO), Public Health Canada, National Institutes of Health (NIH), and the U.S. government developed and deployed Field Decontamination Kits (FDKs), a novel, lightweight, compact, reusable decontamination technology to sterilize Ebola-contaminated medical devices at remote clinical sites lacking infra-structure in crisis-stricken regions of West Africa (medical waste materials are placed in bags and burned). The basis for effectuating sterilization with FDKs is chlorine dioxide (ClO2) produced from a patented invention developed by researchers at the US Army – Natick Soldier RD&E Center (NSRDEC) and commercialized as a dry mixed-chemical for bacterial spore decontamination. In fact, the NSRDEC research scientists developed an ensemble of ClO2 technologies designed for different applications in decontaminating fresh produce; food contact and handling surfaces; personal protective equipment; textiles used in clothing, uniforms, tents, and shelters; graywater recycling; airplanes; surgical instruments; and hard surfaces in latrines, laundries, and deployable medical facilities. These examples demonstrate the far-reaching impact, adaptability, and versatility of these innovative technologies. We present herein the unique attributes of NSRDEC’s novel decontamination technologies and a Case Study of the development of FDKs that were deployed in West Africa by international public health organizations to sterilize Ebola-contaminated medical equipment. FDKs use bacterial spores as indicators of sterility. We review the properties and structures of spores and the mechanisms of bacterial spore inactivation by ClO2. We also review mechanisms of bacterial spore inactivation by novel, emerging, and established nonthermal technologies for food preservation, such as high pressure processing, irradiation, cold plasma, and chemical sanitizers, using an array of B